Giant enhancement and quick stabilization of capacitance in antiferroelectrics by phase transition engineering - Tengfei Hu; Zhengqian Fu; Xiaowei Liu; Linhai Li; Chenhong Xu; YongXin Zhou; Fei Cao; Jiake Xia; Xuefeng Chen; Genshui Wang; Fangfang Xu (Nature Communications, 2024)
Abstract The antiferroelectric-ferroelectric phase transition is a basic principle that holds promise for antiferroelectric ceramics in high capacitance density nonlinear capacitors. So far, the property optimization based on antiferroelectric-ferroelectric transition is solely undertaken by chemical composition tailoring. Alternately, here we propose a phase transition engineering tactic by applying pulsed electric stimulus near the critical electric field, which finally results in ~54.3% enhancement and quick stabilization of capacitance density in Pb0.97La0.02(Zr0.35Sn0.55Ti0.10)O3 antiferroelectric ceramics. Ex-situ and in-situ structural characterizations show that electric stimuli can induce the charming successive structural evolution, including domain evolution from multidomain to monodomain state, and modulation period change from 7.49 to 7.73. Structure-property correlation indicates that the antiferroelectric-ferroelectric phase transition engineering mainly stems from the unexpected irreversible recovery of the modulated structures. The present findings would deepen the understanding of the structural phase transition and provoke composition-independent post-treatment property innovation in the incommensurate antiferroelectric materials and devices.